2016
DOI: 10.1002/2015gc006195
|View full text |Cite
|
Sign up to set email alerts
|

Satellite‐derived surface temperature and in situ measurement at Solfatara of Pozzuoli (Naples, Italy)

Abstract: Ground thermal anomalies in volcanic‐hydrothermal systems, where the outflow of hot fluids gives rise to fumarolic fields, soil degassing, and hot soils, have, up to now, rarely been investigated by using satellite. Here we report a comparison between surface temperature derived by satellite data and a large data set of measured soil temperatures and CO2 fluxes for a volcanic‐hydrothermal system, the Solfatara of Pozzuoli (Campi Flegrei, Italy). Surface temperatures derived from ASTER (Advanced Spaceborne Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Etna [5][6][7][8][9] and in the USA, Hawaiian volcanoes) and the information obtained by this monitoring tool is useful for defining the local hazard level. Moreover, the use of Thermal InfraRed (TIR) satellite sensors is also a consolidated technique [10][11][12][13][14][15][16] for monitoring the volcanic activity at different spatial resolutions: low (e.g., Meteosat Second Generation, MSG, or the Geostationary Environmental Satellite, GOES), moderate (e.g., MODIS, AVHRR, Sentinel 3) and high (e.g., Advanced Spaceborne Thermal Emission and Reflection Radiometer, ASTER, and Landsat 8) [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The development of remote sensing techniques aimed at the estimation of surface temperatures of lava flows, lava lakes, and domes, as well as fumaroles of active volcanic areas, has allowed significant improvements in volcano monitoring activity [6,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Etna [5][6][7][8][9] and in the USA, Hawaiian volcanoes) and the information obtained by this monitoring tool is useful for defining the local hazard level. Moreover, the use of Thermal InfraRed (TIR) satellite sensors is also a consolidated technique [10][11][12][13][14][15][16] for monitoring the volcanic activity at different spatial resolutions: low (e.g., Meteosat Second Generation, MSG, or the Geostationary Environmental Satellite, GOES), moderate (e.g., MODIS, AVHRR, Sentinel 3) and high (e.g., Advanced Spaceborne Thermal Emission and Reflection Radiometer, ASTER, and Landsat 8) [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The development of remote sensing techniques aimed at the estimation of surface temperatures of lava flows, lava lakes, and domes, as well as fumaroles of active volcanic areas, has allowed significant improvements in volcano monitoring activity [6,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Hellman & Ramsey, 2004;Viramonte et al, 2005;Vaughan et al, 2012a;Vaughan et al, 2012b;Silvestri et al, 2016;Braddock et al, 2017;Caudron et al, 2018;Mia et al, 2018a;Mia et al, 2018b. Wright et al, 2010;Favalli et al, 2012;Wadge et al, 2012;Head et al, 2013.…”
Section: Geothermalmentioning
confidence: 99%
“…Several studies have applied RS techniques to study high temperature (>100 °C) fumarolic fields (e.g., [ 16 , 17 , 18 ]); however, the identification of hydrothermal (<100 °C) fumaroles has been challenging [ 19 ]. Nevertheless, a few studies have already shown the use of satellite data to recognize anomalous thermal zones in hydrothermal systems, such as the studies carried out at the Nisyros (Greece) [ 20 ] and Solfatara (Italy) [ 21 ] volcanoes. Changes in the hydrothermal system of the Yellowstone Volcano (USA) were detected through thermal images in 2007; however, visible spectrum images allowed for the first signs of change in vegetation to be identified in 2001 [ 22 ] using high-resolution images.…”
Section: Introductionmentioning
confidence: 99%